Combined effects of chitosan and microencapsulated Enterococcus faecalis CG1.0007 probiotic supplementation on performance and diarrhea incidences in enterotoxigenic Escherichia coli K88(+) challenged piglets - Aluko, Kolawole (Anim Nutr, 2017)
The aim of this study was to investigate the combined effects of chitosan oligosaccharide (COS) and a microencapsulated Enterococcus faecalis CG1.0007 probiotic (PRO) on growth performance and diarrhea incidences in enterotoxigenic Escherichia coli (ETEC) K88(+) challenged piglets in a 14-d study. Thirty piglets, 7.19 ± 0.52 kg initial BW weaned at 21 ± 1 d, were allotted to 5 treatment groups (n = 6) consisting of a corn–soybean meal diet with no additive (negative control, NC), NC + 0.25% chlortetracycline (positive control, PC), NC + 400 mg/kg COS (COS), NC + 100 mg/kg PRO (PRO) and NC + a combination of COS and PRO (CPRO). Pigs were individually housed in cages, acclimated to treatments for a 7-d period and had ad libitum access to feed and water throughout the study. On d 8, pigs were weighed, blood samples were collected, and then orally challenged with 6 mL (1 × 10(11) cfu/mL) of freshly grown ETEC inoculum. During post-challenge period, blood was sampled at 24 and 48 h to determine plasma urea nitrogen (PUN), and diarrhea incidences and fecal consistency scores were recorded from d 9 to 12. On d 14, all pigs were weighed and then euthanized to obtain intestinal tissue samples for histomorphometric measurements. Growth performance responses were similar among treatments during the pre- and post-challenge periods. There were no significant differences in PUN content, incidences of diarrhea, and fecal consistency scores among treatments. The intestinal histomorphology results did not differ significantly among treatments except for PC with increased (P = 0.0001) villus:crypt ratio compared with the NC. Under the conditions of the present study, it can be concluded that supplementation of piglet diets with 400 mg/kg COS, 100 mg/kg microencapsulated PRO or their combination did not significantly improve piglet growth performance both during the pre- and post-ETEC K88(+) oral inoculation. Also, there were no significant reduction of incidences and severity of diarrhea after challenge compared with the control group.